Assessing the impact of defining a global priority research agenda to address HIV‐associated tuberculosis. Issue 11 (31st August 2016) - Odone, Anna; Matteelli, Alberto; Chiesa, Valentina; Cella, Paola; Ferrari, Antonio; Pezzetti, Federica; Signorelli, Carlo; Getahun, Haileyesus
Abstract: Objectives: In 2010, the WHO issued 77 priority research questions (PRQs) to address HIV‐associated TB. Objective of the this study was to assess the impact of defining the research agenda in stimulating and directing research around priority research questions. Methods: We used number and type of scientific publications as a proxy to quantitatively assess the impact of research agenda setting. We conducted 77 single systematic reviews – one for every PRQ – building 77 different search strategies using PRQs' keywords. Multivariate logistic regression models were applied to assess the quantity and quality of research produced over time and accounting for selected covariates. Results: In 2009–2015, PRQs were addressed by 1631 publications (median: 11 studies published per PRQ, range 1–96). The most published area was 'Intensified TB case finding' (median: 23 studies/PRQ, range: 2–74). The majority (62.1%, n = 1013) were published as original studies, and more than half (58%, n = 585) were conducted in the African region. Original studies' publication increased over the study period ( P trend = <0.001). They focused more on the 'Intensified TB case finding' (OR = 2.17, 95% CI: 1.56–2.93) and 'Drug‐resistant TB and HIV infection' (OR = 2.12, 95% CI: 1.47–3.06) areas than non‐original studies. Original studies were published in journals of lower impact factor and received a smaller number of citations than non‐original studies (OR = 0.54, 95% CI: 0.42‐0.69). Conclusion: The generation of evidence to address PRQs has increased over time particularly in selected fields. Setting a priority research agenda for HIV‐associated TB might have positively influenced the direction and the conduct of research and contributed to the global response to such a major threat to health.